Intravitreal Bevacizumab in Non-Arteritic Anterior Ischemic Optic Neuropathy with Bilateral Optic Disc Drusen (A Case Report) - Tayyaba Gul Malik, Muhammad Khalil (Pakistan Journal of Ophthalmology, 2018)
Non-arteritic anterior ischemic optic neuropathy is a vascular disease of optic nerve head. It occurs around 60 years of age and usually associated with hypertension, diabetes, hyperlipidemia and smoking. We present a case of bilateral optic disc drusen with unilateral anterior ischemic optic neuropathy in a 50 years old Asian male. He had history of transient obscuration of vision before he developed non-arteritic anterior ischemic optic neuropathy. Intra vitreal Bevacizumab was given and no improvement was seen in visual acuity after three months of follow-up. Key Words: Optic disc drusen, transient obscuration of vision, non-arteritic anterior ischemic optic neuropathy, optic disc edema, intravitreal Bevacizumab.